Synesthesia for manual alphabet letters and numeral signs in second-language users of signed languages. Issue 4 (3rd July 2016) - Atkinson, Joanna; Lyons, Tanya; Eagleman, David; Woll, Bencie; Ward, Jamie
ABSTRACT: Many synesthetes experience colors when viewing letters or digits. We document, for the first time, an analogous phenomenon among users of signed languages who showed color synesthesia for fingerspelled letters and signed numerals. Four synesthetes experienced colors when they viewed manual letters and numerals (in two cases, colors were subjectively projected on to the hands). There was a correspondence between the colors experienced for written graphemes and their manual counterparts, suggesting that the development of these two types of synesthesia is interdependent despite the fact that these systems are superficially distinct and rely on different perceptual recognition mechanisms in the brain.